Continuous Cropping Alters Multiple Biotic and Abiotic Indicators of Soil Health - Zahida H. Pervaiz; Javed Iqbal; Qingming Zhang; Dima Chen; Hui Wei; Muhammad Saleem (Soil Systems, 2020)
The continuous cropping (CC) of major agricultural, horticultural, and industrial crops is an established practice worldwide, though it has significant soil health-related concerns. However, a combined review of the effects of CC on soil health indicators, in particular omics ones, remains missing. The CC may negatively impact multiple biotic and abiotic indicators of soil health, fertility, and crop yield. It could potentially alter the soil biotic indicators, which include but are not limited to the composition, abundance, diversity, and functioning of soil micro- and macro-organisms, microbial networks, enzyme activities, and soil food web interactions. Moreover, it could also alter various soil abiotic (physicochemical) properties. For instance, it could increase the accumulation of toxic metabolites, salts, and acids, reduce soil aggregation and alter the composition of soil aggregate-size classes, decrease mineralization, soil organic matter, active carbon, and nutrient contents. All these alterations could accelerate soil degradation. Meanwhile, there is still a great need to develop quantitative ranges in soil health indicators to mechanistically predict the impact of CC on soil health and crop yield gaps. Following ecological principles, we strongly highlight the significance of inter-, mixture-, and rotation-cropping with cover crops to sustain soil health and agricultural production.